Berlioz: Scenes from the Life and Work - Bloom, Peter; Bloom, Peter (Book collections on Project MUSE., 2008)
New studies of the great French composer by Jacques Barzun, David Cairns, Jo±l-Marie Fauquet, Hugh Macdonald, Julian Rushton, and other prominent experts. These twelve essays bring new breadth and depth to our knowledge of the life and work of the composer of the Symphonie fantastique. A distinguished international array of scholars here treat such matters as Berlioz's "aesthetics" and what it means to write about the meaning of his music; the political implications of his fiction and the affinities of his projects as composer and as critic; what the Germans thought of his work before his travels in Germany and what the English made of him when he visited their capital city; what he seems to have written immediately after encountering Shakespeare's Romeo and Juliet (a surprise), and where he profited from Beethoven in what later became Rom♭o et Juliette. The volume closes with two reflective essays on Berlioz's literary masterpiece, the M♭moires. Contributors: Lord Aberdare (Alastair Bruce), Jean-Pierre Bartoli, JacquesBarzun, Peter Bloom, David Cairns, Gunther Braam, G♭rard Cond♭, Pepijn van Doesburg, Jo±l-Marie Fauquet, Frank Heidlberger, Hugh Macdonald, and Julian Rushton Peter Bloom (Smith College) is author of The Life of Berlioz (1998) and editor of The Cambridge Companion to Berlioz (2000).